High Systolic Blood Pressure: focus on arterial elasticity - Zh. D. Kobalava; Yu. V. Kotovskaya; M. A. Markova; S. V. Villevalde (Кардиоваскулярная терапия и профилактика)
Aim. Pulse wave velocity (PWV) is a classic index for arterial and aortal elasticity assessment. Aortal PWV is a strong independent predictor of cardiovascular mortality in patients with arterial hypertension (AH). The aim of the study was to investigate arterial elasticity in the elderly AH patients, as well as to assess the effectiveness, safety, and PWV effects of indapamide retard 1,5 mg (Arifon retard) in individuals aged over 80 years. Material and methods. The study included 89 patients aged over 65 years. Using vascular screening system VS-1000 VaSera, Fukuda Denshi, Japan, brachial-ankle PWV (PWVba), carotid-femoral PWV (PWVcf), cardioankle vascular index (CAVI), ankle-brachial index (ABI) were determined. Sixteen patients aged over 80 years, not treated with antihypertensive medications before, were administered Arifon retard (1,5 mg once per day) as 12-week monotherapy. At baseline and in the end of the follow-up period, PWV parameters were measured. Results. Maximal PWV and CAVI values were registered in patients aged over 80 years, comparing to younger participants. There were significant associations between PWVba and age (r=0,49), systolic blood pressure (BP) (r=0,54) and pulse BP (r=0,53), between PWVcf and systolic BP (r=0,62), pulse BP (r=0,66) and diastolic BP (r=- 0,48). There was no correlation between CAVI and BP. Arifon retard treatment associated with significant reduction of systolic and pulse BP, without orthostatic hypotension development, as well as with PWVba and PWVcf decrease. CAVI did not change significantly. Conclusion. In AH patients aged over 80 years, with decreased vascular elasticity, Arifon retard treatment resulted in well-tolerated reduction of systolic BP, pulse BP, and aortal PWV. CAVI was independent of BP level and did not change during the treatment.